Analisis Produktivitas dan Faktor Pengaruh Kinerja Tukang Pemasangan Hebel Menggunakan Productivity Rating (Studi Kasus: Proyek Pembangunan Villa Obao 2, Seminyak, Kuta, Badung) - Silvi, Ni Putu; Putra, I Komang Alit Astrawan; Krisna, I Wayan Dela (Jurnal Ilmiah Rekayasa Sipil, 2024)
The success of each job in a construction project influences the success of the project, where labor productivity factors influence the success of a project. If one project activity has problems, it will greatly affect other project activities because construction project activities are interrelated. Labor management is one of the problems that often causes delays in construction work. The lack of effectiveness of the workforce in carrying out their work makes it very difficult to obtain good productivity values. Smoking, taking breaks and eating during working hours are examples of activities that cause less productive work. Hebel wall installation work is a large volume job and requires a large amount of labor. From the description of the problems found related to labor productivity, this research will carry out an analysis of the productivity of the labor installing hebel installation and the influencing factors of labor productivity installing hebel installation on the construction of the Villa Obao 2 project on Jalan Raya Double Six, Seminyak, Kuta, Badung, Bali. This research uses the Productivity Rating method to determine the value of labor productivity in hebel installation work and distributes questionnaires to analyze factors influencing hebel labor productivity. The results of the analysis of labor productivity observed for 7 days, the average LUR value for workers installing hebel was 67.8% > 50%. Of the 10 factors influencing productivity, only 3 factors have a significant influence on productivity. These factors are the Wage Suitability factor (X3) with an influence value of 4.094, the Motivation factor (X7) with an influence value of 4.133, and the Communication Relations Factor between Employees (X9) with an influence value of 5.498.